Vesicoamniotic Shunting Improves Outcomes in a Subset of Prune Belly Syndrome Patients at a Single Tertiary Center - White, Jeffrey T.; Sheth, Kunj R.; Bilgutay, Aylin N.; Roth, David R.; Austin, Paul F.; Gonzales Jr., Edmond T.; Janzen, Nicolette K.; Tu, Duong D.; Mittal, Angela G.; Koh, Chester J.; Ryan, Sheila L.; Jorgez, Carolina; et al. (Frontiers in Pediatrics, 2018)
Objective: Review outcomes of Prune Belly Syndrome (PBS) with the hypothesis that contemporary management improves mortality. Methods: A retrospective chart review of inpatient and outpatient PBS patients referred between 2000 and 2018 was conducted to assess outcomes at our institution. Data collected included age at diagnosis, concomitant medical conditions, imaging, operative management, length of follow-up, and renal function. Results: Forty-four PBS patients presented during these 18 years. Prenatal diagnoses were made in 17 (38%); 65% of these patients underwent prenatal intervention. The remaining patients were diagnosed in the infant period (20, 44%) or after one year of age (8, 18%). Twelve patients died from cardiopulmonary complications in the neonatal period; the neonatal mortality rate was 27%. The mean follow-up among patients surviving the neonatal period was 84 months. Forty-two patients had at least one renal ultrasound (RUS); of the 30 patients with NICU renal ultrasounds, 26 (87%) had hydronephrosis and/or ureterectasis. Of the 18 patients who underwent voiding cystourethrogram (VCUG), 16 (89%) demonstrated VUR. Fifty-nine percent had respiratory distress. Nine patients (20%) were oxygen-dependent by completion of follow up. Thirty-eight patients (84%) had other congenital malformations including genitourinary (GU) 67%, gastrointestinal (GI) 51%, and cardiac 47%. Sixteen patients (36%) had chronic kidney disease (CKD) of at least stage 3; 3 patients (7%) had received renal transplants. Eighty percent of patients had at least one surgery (mean 2.2, range 0-7). The most common was orchiopexy (71%). The next most common surgeries were vesicostomy (39%), ureteral reimplants (32%), abdominoplasty (29%), nephrectomy (25%), and appendicovesicostomy (21%). After stratifying patients according to Woodard classification, a trend for 12% improvement in mortality after VAS was noted in the Woodard Classification 1 cohort. Conclusions: PBS patients frequently have multiple congenital anomalies. Pulmonary complications are prevalent in the neonate while CKD (36%) is prevalent during late childhood. The risk of CKD increased significantly with the presence of other congenital anomalies in our cohort. Mortality in childhood is most common in infancy and may be as low as 27%. Contemporary management of PBS, including prenatal interventions, reduced the neonatal mortality rate in a subset of our cohort.